Impact on rutting from introduction of increased axle loads in Finland. Issue 13 (10th November 2021) - Ekblad, Jonas; Lundström, Robert; Karlsson, Robert; Valtonen, Jarkko
ABSTRACT: In 2013, Finland introduced legislation increasing gross vehicle weights (GVW) on a number of trucks. Since the actual impact on road damage is nearly impossible to quantify in advance, the present analysis of road surface measurements is intended to provide knowledge regarding the impact on road damage. Rutting is influenced by many conflated phenomena. To indicate and capture the effect on road damage due to the new maximum GVW for certain truck- and trailer combinations, the analysis follows two different but mutually supporting lines of reasoning, empirical and theoretical, respectively. Analysis of measured rut depth is supported by theoretical calculations. Theoretical findings clearly indicate that the relative increase in road damage induced by higher GVW is larger than the increase in relative payload capacity. There was a rapid fleet shift towards heavier trucks after 2013, and statistical (empirical) analysis of road surface measurements shows an increase in rutting after this introduction.